2015
DOI: 10.1007/s00300-015-1828-3
|View full text |Cite
|
Sign up to set email alerts
|

Working on a baseline for the Kongsfjorden food web: production and properties of macroalgal particulate organic matter (POM)

Abstract: Macroalgae, in particular kelps, produce a large amount of biomass in Kongsfjorden, which is to a great extent released into the water in an annual cycle. As an example, the brown alga Alaria esculenta loses its blade gradually, 3 ± 0.8 % of the blade area per day (August 2012), thereby adding to the pool of particulate organic matter (POM) in the fjord. Upon release small thallus pieces are ''aging'' in that they are prone to leaching and serving as substrate for microorganisms, thus turning into palatable fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…As an example, the brown alga Alaria esculenta loses its blade gradually, 3 ± 0.8 % of the blade area per day during the autumn (2012), thereby adding to the pool of particulate organic matter (POM) in the fjord (Buchholz and Wiencke 2015). This is interesting because in their preliminary feeding experiment, the mysid Mysis oculata was shown to ingest artificially produced POM (aPOM) from Alaria esculenta, and ingestion of aPOM was also demonstrated in the bivalve Hiatella arctica.…”
Section: Partmentioning
confidence: 99%
See 1 more Smart Citation
“…As an example, the brown alga Alaria esculenta loses its blade gradually, 3 ± 0.8 % of the blade area per day during the autumn (2012), thereby adding to the pool of particulate organic matter (POM) in the fjord (Buchholz and Wiencke 2015). This is interesting because in their preliminary feeding experiment, the mysid Mysis oculata was shown to ingest artificially produced POM (aPOM) from Alaria esculenta, and ingestion of aPOM was also demonstrated in the bivalve Hiatella arctica.…”
Section: Partmentioning
confidence: 99%
“…They detected no consistent differences in meio-and macrofaunal density, diversity or composition during the year, although possible responses to spring food supply in meiofaunal reproduction were observed in Nematoda, Harpacticoida and macrobenthic Crustacea. They concluded that the resilience of the benthic community to marked seasonality in pelagic phytodetritus fluxes may be related to organic matter reserves in sediments, inclusion of macroalgal carbon into the diet (see also Buchholz and Wiencke 2015) and employment of lecitotrophic larva or direct development by polar benthos.…”
Section: Partmentioning
confidence: 99%
“…−1.5‰ to 1.5‰), and generally fall within the range of live kelps (Fig. 6; Stephenson et al 1986, Markel and Shurin 2015, Buchholz and Wiencke 2016, Buchholz et al 2019, Gabara 2020. We suspect this is the main route through which kelp-derived energy supports consumers for two reasons.…”
Section: Energy Flow and Kelp Utilization By Consumersmentioning
confidence: 87%
“…The high abundance of the former due to the fact that this bacterium prefers to utilize complex organic matter by directly attaching to algal cells and algal derivative clastic particles (Y. Li et al 2018), while the fresh water of S5 is more conducive to the growth of algae (Buchholz Wiencke 2016), so salinity indirectly affects the abundance of Flavobacteriaceae. The high abundance of Vibrionaceae can be ascribed to its association with soil microbiota (Reen et al 2006), suggesting that Vibrionaceae may be terrigenous microorganism, which are imported into the fjords by glacial meltwater and are subjected to salinity stress, which is not so abundant in high-salinity areas.…”
Section: Effect Of Salinity On Bacterial Communitymentioning
confidence: 99%